Controlling and exploiting phases in multi-spin systems using electron spin resonance and nuclear magnetic resonance. - Simmons, S; Wu, H; Morton, J (2012)
The phase of a superposition state is a quintessential characteristic that differentiates a quantum bit of information from a classical one. This phase can be manipulated dynamically or geometrically, and can be exploited to sensitively estimate Hamiltonian parameters, perform faithful quantum state tomography and encode quantum information into multiple modes of an ensemble. Here we discuss the methods that we have employed to manipulate and exploit the phase information of single-, two-, multi-qubit and multi-mode spin systems.